2021
DOI: 10.1088/1757-899x/1074/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Detection of intruder using the improved dragonfly optimization algorithm

Abstract: Now a days, we are completely dependent on the systems and also on the internet. Most of our valuable information is stored in the system or in the cloud. So, it’s very necessary to protect our data and also our system from the outside intruders and also from the intruders already entered into our system. To protect our system, intrusion detection systems are constructed using many traditional techniques. Some of them are decision tree, KDD, data mining techniques, Artificial Neural Network. But there are many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Te F-measure also shows promising results in comparison to other techniques for R2L attacks. (9) If Maximum > 1 (10) For J in range (Selected Data, Row) (11) If Selected Data (J) = = 0 (12) Normalized Data (J, I) � 0 (13) Else (14) Normalized Data (J, I)�(Selected Data (J)-Minimum)/(Maximum-Minimum) (15) End-If (16) End-For (17) Else (18) For J in range (Selected Data, Row) (19) Normalized Data (J, I) � Selected Data (J) (20)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Te F-measure also shows promising results in comparison to other techniques for R2L attacks. (9) If Maximum > 1 (10) For J in range (Selected Data, Row) (11) If Selected Data (J) = = 0 (12) Normalized Data (J, I) � 0 (13) Else (14) Normalized Data (J, I)�(Selected Data (J)-Minimum)/(Maximum-Minimum) (15) End-If (16) End-For (17) Else (18) For J in range (Selected Data, Row) (19) Normalized Data (J, I) � Selected Data (J) (20)…”
Section: Resultsmentioning
confidence: 99%
“…But, the drawback of the study is the requirement of the module to use the integrated system that detects the attacks for updated data logs. Devarakonda et al integrated the HIDS and NIDS and implemented the improved dragonfy optimization technique [10]. Te detection rate was 96% but limited to determining the attacks for desired results in terms of precision.…”
Section: Introductionmentioning
confidence: 99%
“…Fitness function is introduced to check the accuracy of the function. Devarakonda et al [15] showed the usage of improvised dragonfly optimization algorithm. The convergence and fitness function are added to the traditional dragonfly optimization algorithm.…”
Section: Literature Surveymentioning
confidence: 99%
“…Recently, researchers from various domains applied meta-heuristic algorithms to FS. Some of the recent works that used metaheuristic algorithms for FS in IDS are: Genetic Algorithm (GA) [7], Bat Optimization algorithm (BOA) [10], Particle Swarm Optimization (PSO) [8], Dragonfly Algorithm (DA) [11], Grey Wolf Optimization (GWO) [9], Firefly optimization (FFO) [12], whale optimization algorithm (WOA) [13] and Pigeon Inspired Optimizer (PIO) [14]. Among them, Alazzam et al [14] proposed a PIO to select the prominent features by eradicating the redundant features.…”
Section: Introductionmentioning
confidence: 99%